Lipid consumption in coral larvae differs among sites: a consideration of environmental history in a global ocean change scenario. Issue 1853 (26th April 2017) - Rivest, Emily B.; Chen, Chii-Shiarng; Fan, Tung-Yung; Li, Hsing-Hui; Hofmann, Gretchen E.
Abstract : The success of early life-history stages is an environmentally sensitive bottleneck for many marine invertebrates. Responses of larvae to environmental stress may vary due to differences in maternal investment of energy stores and acclimatization/adaptation of a population to local environmental conditions. In this study, we compared two populations from sites with different environmental regimes (Moorea and Taiwan). We assessed the responses of Pocillopora damicornis larvae to two future co-occurring environmental stressors: elevated temperature and ocean acidification. Larvae from Taiwan were more sensitive to temperature, producing fewer energy-storage lipids under high temperature. In general, planulae in Moorea and Taiwan responded similarly to p CO2 . Additionally, corals in the study sites with different environments produced larvae with different initial traits, which may have shaped the different physiological responses observed. Notably, under ambient conditions, planulae in Taiwan increased their stores of wax ester and triacylglycerol in general over the first 24 h of their dispersal, whereas planulae from Moorea consumed energy-storage lipids in all cases. Comparisons of physiological responses of P. damicornis larvae to conditions of ocean acidification and warming between sites across the species' biogeographic range illuminates the variety of physiological responses maintained within P. damicornis, which may enhance the overall persistence of this species in the light of global climate change.